Regional resilience: A critical examination of the ecological framework - Todd Swanstrom (University of California, Institute of Urban and Regional Development (IURD), 2008)
The different responses of New York City to the terrorist attacks in 2001 and New Orleans following Hurricane Katrina in 2005 have focused the attention of scholars on the ability of metropolitan areas to recover from disasters. In the case of New York City, despite dire warnings that people would flee urban settings that were vulnerable to terrorist attacks, the real estate market in lower Manhattan revived and is now as vibrant as ever. The painful memory remains, but the city has recovered from its wounds. New Orleans is another story. The immediate response to the hurricane was often uncoordinated and ineffectual. The long-run recovery has been slow and uneven. The population of the city is still only at about 72 percent of its pre-Katrina level and while the levees have been repaired they have not been built to withstand a category 5 hurricane like Katrina. It is still uncertain as to whether the city will recover enough to sustain the dynamic culture in food, music, and the arts that flourished before Katrina. The word that is increasingly used to describe successful responses to disasters like these is resilience. Resilience is an idea that can also be applied to slowly developing challenges as well as sudden disasters. The purpose of this paper is to explore the value of the resilience framework for thinking about how metropolitan areas respond to challenges.1 At this point in its applications to regional studies, resilience is more than a metaphor but less than a theory. At best it is a conceptual framework that helps us to think about regions in new ways, i.e., dynamically and holistically. As derived from the field of systems ecology, the resilience framework encourages us to think about regions as interconnected systems with extensive feedback processes that must be understood for successful human intervention.
Keywords: 330